Anomalies in the Charge Yields of Fission Fragments from the U ( n , f ) 238 Reaction - Wilson, J. N.; Lebois, M.; Qi, L.; Amador-Celdran, P.; Bleuel, D.; Briz, J. A.; Carroll, R.; Catford, W.; De Witte, H.; Doherty, D. T.; Eloirdi, R.; Georgiev, G.; et al. (Physical review letters, 2017)
Fast-neutron-induced fission of 238U at an energy just above the fission threshold is studied with a novel technique which involves the coupling of a high-efficiency γ-ray spectrometer (MINIBALL) to an inverse-kinematics neutron source (LICORNE) to extract charge yields of fission fragments via γ-γ coincidence spectroscopy. Experimental data and fission models are compared and found to be in reasonable agreement for many nuclei; however, significant discrepancies of up to 600% are observed, particularly for isotopes of Sn and Mo. This indicates that these models significantly overestimate the standard 1 fission mode and suggests that spherical shell effects in the nascent fission fragments are less important for low-energy fast-neutron-induced fission than for thermal neutron-induced fission. Finally, this has consequences for understanding and modeling the fission process, for experimental nuclear structure studies of the most neutron-rich nuclei, for future energy applications (e.g., Generation IV reactors which use fast-neutron spectra), and for the reactor antineutrino anomaly.